A Comparison of MALL Listening Input Modes for Immersive Self-Learning Among EFL Learners in China - Tian, Xinran; Ng, Boon Sim; Halim, Hazlina Abdul; Sun, Jiali (Journal of Ecohumanism, 2025)
This study seeks to explore how differed MALL listening input modes would affect immersive self-learning among English learners in China. A combination of qualitative and quantitative research method is used among 30 first-year university students with a major of English. Through quasi-experimental design and structured interview as well as Mean (x), standard deviation (S.D.), t-test dependable, and content analysis, critical findings are drawn. The study results indicate that video, video and audio as well as video and ASR text input modes could affect incidental vocabulary acquisition and listening comprehension, as moderated by self efficacy and preferred listening style. This research provides insights for EFL students in immersive self-learning.